Proceedings of the 2007 ACM CoNEXT Conference on - CoNEXT '07 2007
DOI: 10.1145/1364654.1364667
|View full text |Cite
|
Sign up to set email alerts
|

Multipath code casting for wireless mesh networks

Abstract: Designing high throughput wireless mesh networks involves solving interrelated scheduling, routing, and interference problems. In this paper, we exploit the broadcast properties and the path diversity of wireless meshes to implement an efficient multipath routing protocol, Multipath Code Casting (MC 2 ).In contrast to prior work in opportunistic routing, which required strong coordination across nodes to prevent information repetition, our design is based on network coding and does not require node coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Recent studies have shown the importance of adding rate control to NC-based unicast routing protocols, which exploit MAC layer broadcast [30], [32]. However, end-to-end rate control in multicast is much more complex than in unicast, and there is no widely accepted solution so far.…”
Section: B Source Rate Limitingmentioning
confidence: 99%
“…Recent studies have shown the importance of adding rate control to NC-based unicast routing protocols, which exploit MAC layer broadcast [30], [32]. However, end-to-end rate control in multicast is much more complex than in unicast, and there is no widely accepted solution so far.…”
Section: B Source Rate Limitingmentioning
confidence: 99%
“…We enhance Glomosim to use a trace-driven physical layer based on traces from the real-world link quality measurements in the MIT Roofnet [2], an experimental 802.11b/g mesh network of 38 nodes widely used in research papers [20,10]. We use 802.11 MAC with 5.5Mbps raw bandwidth and 250 meter nominal range.…”
Section: Methodsmentioning
confidence: 99%
“…While ExOR and MORE individually outperform shortest-path routing, ExOR is known to poorly exploit spatial reuse due to its stringent scheduling (see [5], [10]), and MORE is vulnerable to the deviation of link-level measurements due to its credit-based forwarding approach (see our analysis in Section III-B). We argue that by carefully combining their key components, SOR not only removes the limitations of ExOR and MORE, but also becomes fundamentally robust toward inaccurate link-level measurements.…”
Section: In This Paper We Design a Robust Wireless Mesh Routing Protmentioning
confidence: 99%
“…If the link-level measurements are inaccurate or cannot adapt quickly enough to the current network condition, forwarders may receive too few (or too many) credits, leading to insufficient (or overloaded) transmissions and hence degraded throughput. Extensions of MORE include MC 2 [10] and CodeOR [20], yet they still use the previously measured link delivery probabilities to compute the expected number of packets to be forwarded.…”
Section: Related Workmentioning
confidence: 99%